2019
DOI: 10.1101/678284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroanatomical Changes in White and Grey Matter after Sleeve Gastrectomy

Abstract: Background: MRI studies show that obese adults have reduced grey (GM) and white matter (WM) tissue density as well as altered WM integrity. It remains to be examined if bariatric surgery induces structural brain changes. The aim of this study is to characterize GM and WM density changes in a longitudinal setting, comparing pre-and post-operation and to determine whether these changes are related to inflammation and cardiometabolic markers. Methods: 29 severely obese participants (age: 45.9±7.8 years) scheduled… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…To support the idea that the effects of bariatric surgery represent a resolution of adiposity-related brain abnormalities, we previously investigated whether the brain regions that show improvements after bariatric surgery are also different between individuals who are severely obese and those who are lean. Using an independent dataset from the Human Connectome Project (HCP), we found that changes in brain morphometry observed following surgery overlapped with brain differences between the obese and normal weight states, in line with the hypothesis that weight loss and/or concomitant improvement of metabolic/inflammatory alterations could be responsible for the post-operative changes in the areas previously impacted by obesity (29). Previous studies have also suggested that post-operative changes in WM and GM densities could be attributed to neural plasticity (30), recovery of brain integrity (31,32), or changes in the composition of fiber tracts (30).…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…To support the idea that the effects of bariatric surgery represent a resolution of adiposity-related brain abnormalities, we previously investigated whether the brain regions that show improvements after bariatric surgery are also different between individuals who are severely obese and those who are lean. Using an independent dataset from the Human Connectome Project (HCP), we found that changes in brain morphometry observed following surgery overlapped with brain differences between the obese and normal weight states, in line with the hypothesis that weight loss and/or concomitant improvement of metabolic/inflammatory alterations could be responsible for the post-operative changes in the areas previously impacted by obesity (29). Previous studies have also suggested that post-operative changes in WM and GM densities could be attributed to neural plasticity (30), recovery of brain integrity (31,32), or changes in the composition of fiber tracts (30).…”
Section: Introductionsupporting
confidence: 62%
“…Our recent findings (29) confirmed the results of three studies showing an increase in WM and GM densities following bariatric surgery (30)(31)(32). These GM and WM increases were most pronounced and widespread 12 months after the surgery, and were significantly associated with post-operative weight loss and improvement of metabolic/inflammatory variables (29). To support the idea that the effects of bariatric surgery represent a resolution of adiposity-related brain abnormalities, we previously investigated whether the brain regions that show improvements after bariatric surgery are also different between individuals who are severely obese and those who are lean.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Grey matter density was assessed from each T1-weighted MRI using a standard voxel-based morphometry pipeline [ 28 , 52 ]. The preprocessing steps were the following: (1) image denoising [ 53 ]; (2) intensity non-uniformity correction [ 54 ]; and (3) image intensity normalization into range (0–100) using histogram matching.…”
Section: Methodsmentioning
confidence: 99%